Supporting rural entrepreneurship in the UK microbrewery sector. Issue 11 (2nd November 2015) - Ellis, Victoria; Bosworth, Gary
Abstract : Purpose: – The UK has seen rapid growth in the number of microbreweries but a concurrent decline in public house numbers raising concerns about the sustainability of this growth. The purpose of this paper is to explore the impact of funding upon competition in the sector and the entrepreneurial characteristics of microbrewers. With an emphasis on rural-based businesses, the local economic impacts are also examined. Design/methodology/approach: – The research is informed by analysis of trends in both the brewing and public house sectors in the UK. Semi-structured interviews were carried out with microbrewers, including five who had received funding to support their development. These were supplemented with three days of participant observation at collaborative brewing events with 26 microbrewery owners and three microbrewery managers. Findings: – The findings indicate that the value attached to microbreweries extends beyond their economic contribution with wider outcomes including training and job creation, the preservation of listed buildings and the enhancement of rural tourism. Funding stimulated entrepreneurial responses but support for these wider outcomes ran the risk of distorting competition. Originality/value: – As competition increases in the sector, microbrewery owners need to become more entrepreneurial to maintain their market position. Competition is heightened by a number of lifestyle enterprises that can survive with lower profit levels while routes to market are limited by a decline in the public house sector. In such a pressured market, there is a need for clearer assessments of the impacts on local economies and entrepreneurship when grant funding is provided.